IMAGERY WORLD OF DARIIA YAROSLAVSKA’S NOVELLA COLLECTION “THE BANNER” - Касіян, З. Л. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article deals with the analysis of ideo-thematic and genre and style features of novellas «The Banner» by Ukrainian diaspora writer Dariia Yaroslavska. Peculiarity of the style of the collection is clear “lyrization” of the narration, which is typical also for the writer’s short prose of the early period. There has been proved the genetic root of Dariia Yaroslavska’s artistic thinking in the traditions and innovations of the short novella writing in Western Ukraine in the 1920-s–1930-s.